Association of Premature Rupture of Membrane and Urinary Tract Infection among Pregnant Women (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Prelabour rupture of membranes among pregnant women is a common obstetrics problem encountered by the obstetricians.Objective: This present study was aimed to see the association of premature rupture of membrane and urinary tract infection among pregnant women.Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Enam Medical College, Savar, Dhaka, Bangladesh from January 2022 to December 2022 for a period of one year. Pregnant women with preterm premature rupture of membrane who were admitted in the Department of Obstetrics & Gynaecology at Enam Medical College, Savar, Dhaka, Bangladesh were selected as study population. Gravid women both primi & multi with preterm premature rupture of membrane, pregnancy of more than 23 weeks’ duration & less than 37 weeks or spontaneous rupture of the membranes were included in this study. All the clinical parameters, feto-maternal outcomes were recorded.Results: A total number of 83 pregnant women presented with premature rupture of membrane were recruited for this study. The mean with SD of the study population were 25.3±4.46 years with the range of 17 to 38 years. The most common comorbidities among the study population was urinary tract infection which was 78(94.0%) cases. In this study previous history of cesarean section was found in 28(33.7%) cases.Conclusion: In conclusion women presented with premature rupture of membrane is significantly associated with urinary tract infection.Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):32-37